Peer Group WhatsApp Can Enhances Knowledge And Attitude About Sanitary Pads in Adolescent Girls - Abriani, Yohana Dewi; Asmawati, Asmawati; Mardiani, Mardiani (Poltekkes Kemenkes Palu, 2025)
Introduction: Currently, many women still do not know what kind of pads are safe to use. Errors in choice and use of pads can hurt reproductive health. Purpose: Knowing the influence of peer group education WhatsApp (PGEW) on promoting knowledge and attitude (KA) about sanitary pads. Methods: The type of research is a quasi-experiment pre-and post-test with a control group; the samples are 30 people in each group; the sampling technique is consecutive sampling; Data of (KA) have been collected by filling out questionnaires, and research has been conducted for 3–4 months Education in the intervention group is done via WhatsApp, while education in the control group is done via a module. The statistical test used T-Independent test. Results: There was an increase in the average knowledge of 10.26 from (67.44-77.69, p-value <0.001), and there was an increase in the average attitude of 4.18 from (50.48-54.65, p-value 0.024). Independent T-tests showed that there was a difference in average knowledge around 7.436 (p-value 0.014< α 0.05) and there is a difference in average attitude around 8.360 (p-value 0.027< α 0.05). Conclusion: The PGEW method is effectively used to improve the (KA) of adolescents about sanitary pads.